Epigenetic inactivation of IRX4 is responsible for acceleration of cell growth in human pancreatic cancer. Issue 12 (14th October 2020) - Chakma, Kanchan; Gu, Zhaodi; Abudurexiti, Yakefujiang; Hata, Tatsuo; Motoi, Fuyuhiko; Unno, Michiaki; Horii, Akira; Fukushige, Shinichi
Abstract: Epigenetic gene silencing by aberrant DNA methylation is one of the important mechanisms leading to loss of key cellular pathways in tumorigenesis. Methyl‐CpG‐targeted transcriptional activation (MeTA) reactivates hypermethylation‐mediated silenced genes in a different way from DNA‐demethylating agents. Microarray coupled with MeTA (MeTA‐array) identified seven commonly hypermethylation‐mediated silenced genes in 12 pancreatic ductal adenocarcinoma (PDAC) cell lines. Among these, we focused on IRX4 (Iroquois homeobox 4) because IRX4 is located at chromosome 5p15.33 where PDAC susceptibility loci have been identified through genome‐wide association study. IRX4 was greatly downregulated in all of the analyzed 12 PDAC cell lines by promoter hypermethylation. In addition, the IRX4 promoter region was found to be frequently and specifically hypermethylated in primary resected PDACs (18/28: 64%). Reexpression of IRX4 inhibited colony formation and proliferation in two PDAC cell lines, PK‐1 and PK‐9. In contrast, knockdown of IRX4 accelerated cell proliferation in an IRX4 ‐expressing normal pancreatic ductal epithelial cell line, HPDE‐1. Because IRX4 is a sequence‐specific transcription factor, downstream molecules of IRX4 were pursued by microarray analyses utilizing tetracycline‐mediated IRX4 inducible PK‐1 and PK‐9 cells; CRYAB, CD69, and IL32 were identified as IRX4 downstream candidate genes. Forced expression of these genes suppressed colony formation abilities for both PK‐1 and PK‐9. These results suggest that DNA methylation‐mediated silencing of IRX4 contributes to pancreatic tumorigenesis through aberrant transcriptional regulation of several cancer‐related genes. Abstract : IRX4 was found as a commonly hypermethylation‐mediated silenced gene in pancreatic ductal adenocarcinoma (PDAC) using the methyl‐CpG targeted transcriptional activation (MeTA) method. Promoter hypermethylation of IRX4 was seen in PDAC, reexpression of IRX4 inhibited proliferation in PDAC cell lines, and forced expression of IRX4 downstream genes suppressed colony formation abilities. These results suggest that DNA methylation‐mediated silencing of IRX4 contributes to pancreatic tumorigenesis through aberrant transcriptional regulation of several cancer‐related genes.